A new 400-kD protein from isolated adherens junctions: its localization at the undercoat of adherens junctions and at microfilament bundles such as stress fibers and circumferential bundles (The Rockefeller University Press, 1989)
In the previous study, we succeeded in isolating the cell-to-cell adherens junctions from rat liver (Tsukita, S., and S. Tsukita. 1989. J. Cell Biol. 108:31-41.). In this study, we have obtained mAbs specific to the 400-kD protein, which was identified as one of the major constituents of the undercoat of isolated adherens junctions. Immune blot analyses showed that this protein occurs in various types of tissues. Immunofluorescence microscopy and immune electron microscopy have revealed that this protein is distributed not only at the undercoat of adherens junctions but also along actin bundles associated with the junction in nonmuscle cells: stress fibers in cultured fibroblasts and circumferential bundles in epithelial cells. The partially purified protein molecule looks like a slender rod approximately 400 nm in length. By virtue of its molecular shape, we have named this protein 'tenuin' (from Latin 'tenuis', thin or slender).